Spatial Patterns of Sea Surface Temperature Influences on East African Precipitation as Revealed by Empirical Orthogonal Teleconnections - Appelhans, Tim; Nauss, Thomas (Frontiers in Earth Science, 2016)
East Africa is characterized by a rather dry annual precipitation climatology with two distinct rainy seasons. In order to investigate sea surface temperature driven precipitation anomalies for the region we use the algorithm of empirical orthogonal teleconnection analysis as a data mining tool. We investigate the entire East African domain as well as 5 smaller sub-regions mainly located in areas of mountainous terrain. In searching for influential sea surface temperature patterns we do not focus any particular season or oceanic region. Furthermore, we investigate different time lags from zero to twelve months. The strongest influence is identified for the immediate (i.e. non-lagged) influences of the Indian Ocean in close vicinity to the East African coast. None of the most important modes are located in the tropical Pacific Ocean, though the region is sometimes coupled with the Indian Ocean basin. Furthermore, we identify a region in the southern Indian Ocean around the Kerguelen Plateau which has not yet been reported in the literature with regard to precipitation modulation in East Africa. Finally, it is observed that not all regions in East Africa are equally influenced by the identified patterns.